Repurposing of High-Dose Erythropoietin as a Potential Drug Attenuates Sepsis in Preconditioning Renal Injury - Wiwat Chancharoenthana; Kanyarat Udompronpitak; Yolradee Manochantr; Piyawat Kantagowit; Ponthakorn Kaewkanha; Jiraporn Issara-Amphorn; Asada Leelahavanichkul (Cells, 2021)
Due to (i) the uremia-enhanced sepsis severity, (ii) the high prevalence of sepsis with pre-existing renal injury and (iii) the non-erythropoiesis immunomodulation of erythropoietin (EPO), EPO was tested in sepsis with pre-existing renal injury models with the retrospective exploration in patients. Then, EPO was subcutaneously administered in mice with (i) cecal ligation and puncture (CLP) after renal injury including 5/6 nephrectomy (5/6Nx-CLP) and bilateral nephrectomy (BiNx-CLP) or sham surgery (sham-CLP) and (ii) lipopolysaccharide (LPS) injection, along with testing in macrophages. In patients, the data of EPO administration and the disease characteristics in patients with sepsis-induced acute kidney injury (sepsis-AKI) were evaluated. As such, increased endogenous EPO was demonstrated in all sepsis models, including BiNx-CLP despite the reduced liver erythropoietin receptor (EPOR), using Western blot analysis and gene expression, in liver (partly through hepatocyte apoptosis). A high-dose EPO, but not a low-dose, attenuated sepsis in mouse models as determined by mortality and serum inflammatory cytokines. Furthermore, EPO attenuated inflammatory responses in LPS-activated macrophages as determined by supernatant cytokines and the expression of several inflammatory genes (iNOS, IL-1β, STAT3 and NFκB). In parallel, patients with sepsis-AKI who were treated with the high-dose EPO showed favorable outcomes, particularly the 29-day mortality rate. In conclusion, high-dose EPO attenuated sepsis with preconditioning renal injury in mice possibly through the macrophage anti-inflammatory effect, which might be beneficial in some patients.